(NwIOLON^ELXNYJ KONCERT d(B. (N{OSTAKOWI^As (NpOQSNENIEs - (Nt(B.(NbOGDANOWAs ((NmOSKWAs (NsOWETSKIJ kOMPOZITORs, 1960)
(NkONCERTOW DLQ WIOLON^ELI S ORKESTROM NAPISANO SRAWNITELXNO NEMNOGO(B, (NMENX[E ^EM FORTEPIANNYH ILI SKRIPI^NIH(B.(Nw OTLI^IE OT FORTEPXQNO I SKRIPKI(B. (NWIOLON^ELI(B-(NWYHODCU IZ ORKESTRA(B.s
Keywords: (NmONOGRAFIQs